The Moonshine Policy: The Idiosyncrasy Factors of President Moon Jae-In in Improving Inter-Korean Relations - Sinuraya, Bella Wardha Devita; Munabari, Fahlesa (Intermestic: Journal of International Studies, 2023)
The North Korea's nuclear program has threatened the security of the Korean Peninsula. Every year, North Korea launches various types of missile tests, which raises the international community's concern. As a country responsible for maintaining security on the Korean Peninsula, South Korea has made various efforts to stop North Korea's nuclear development. Foreign policy issued by South Korea is constantly re-orientated according to the identity and perspective of the South Korean president at a particular time. This article analyzes President Moon Jae In's idiosyncrasy factors informing the new Sunshine policy to resolve North Korea's nuclear threats. This study aims to prove that the idiosyncratic factor has a significant influence on the decision-making process and the formation of the South Korea’s foreign policy. It shows that President Moon Jae In is a conciliatory leader who has an active-independent leadership characteristic based on the current dynamic North and South Korea’s nuclear tensions.